1997
DOI: 10.1038/sj.ejcn.1600451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased fruit and vegetable intake on the susceptibility of lipoprotein to oxidation in smokers

Abstract: Objective: To evaluate the effect of an increased dietary intake of fruit and vegetables on susceptibility of LDL to oxidation in smokers and nonsmokers. Design: A descriptive and prospective study. Setting: Joseph Fourier University, Grenoble. Subjects: Volunteers were age and sex matched in the smoking and nonsmoking groups and were recruited by announcement.Interventions: Increased intake of fruits and vegetables for two weeks providing 30 mgaday of carotenoids. Main outcome measures: Circulating levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
29
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 41 publications
11
29
1
1
Order By: Relevance
“…We also found a negative linear regression between age and TBARS levels (r ¼ À0.20; P ¼ 0.01), whereas others have reported a positive correlation between age and TBARS levels (Junqueira et al, 2004). In agreement with the present findings, some studies did not report a modified production of lipoperoxides with advancing age (Hininger et al, 1997;Savarino et al, 2001). The impact of age at enrolment in these different studies and those of lifestyle factors might explain the discrepancies between the studies.…”
Section: Discussionsupporting
confidence: 87%
“…We also found a negative linear regression between age and TBARS levels (r ¼ À0.20; P ¼ 0.01), whereas others have reported a positive correlation between age and TBARS levels (Junqueira et al, 2004). In agreement with the present findings, some studies did not report a modified production of lipoperoxides with advancing age (Hininger et al, 1997;Savarino et al, 2001). The impact of age at enrolment in these different studies and those of lifestyle factors might explain the discrepancies between the studies.…”
Section: Discussionsupporting
confidence: 87%
“…A similar increase was observed by Hininger et al (1997), who supplemented smokers with a variety of carotenoid-rich vegetables. In our study, these LDL changes coincided with significant increases in the plasma concentrations of lutein, b-cryptoxanthin, a-carotene and b-carotene.…”
Section: Discussionsupporting
confidence: 77%
“…The sample size was based on a power calculation using LDL lag time increases observed in a previous study with similar protocol (Hininger et al, 1997). A one-tailed t-test confirmed that 16 subjects would give 80% power to detect a 7 min change in LDL lag time at the 5% significance level.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocyte GPX and SOD activities depend largely on the method used for their determination. The activities obtained in Cuban subjects were in the range of previous values observed in French adults using the same methods (Hininger et al, 1997;Preziosi et al, 1998;Roussel et al, 1998). These results agree with the reported lack of effect of energyrestricted diet on GPX and SOD activities in experimental conditions (Velthuis-te Wierick et al, 1995).…”
Section: Discussionsupporting
confidence: 81%